2013
DOI: 10.9790/0853-1135862
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection in pediatrics patients in north India

Abstract: Background -Urinary tract infection (UTI) is one of the most common bacterial infections

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
2
10
1
Order By: Relevance
“…Males outnumbered females by a smaller proportion except in the 5-12 year age group with a male: female ratio of 1:1.3. The predominance of males in our study was not consistent with many previous reports where females, except during infancy, were more affected than the males 9,[13][14][15][16] . Reasons may be the smaller sample size and increased preference for seeking treatment for only the male child in certain communities.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Males outnumbered females by a smaller proportion except in the 5-12 year age group with a male: female ratio of 1:1.3. The predominance of males in our study was not consistent with many previous reports where females, except during infancy, were more affected than the males 9,[13][14][15][16] . Reasons may be the smaller sample size and increased preference for seeking treatment for only the male child in certain communities.…”
Section: Discussioncontrasting
confidence: 99%
“…After fever (69.2%) and excessive crying/ irritability (29.1%), urinary symptoms like dysuria (27.7%) and increased frequency of micturition (27.7%) predominated. Other studies also indicated high association between fever and UTI [8][9][10][11][12][13][15][16][17] . According to the World Health Organisation (WHO), fever as a marker of UTI has a sensitivity of 80% and specificity of 40% 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In contrast, a study done by Patel et al and Gupta et al, E. coli was found to be most sensitive to imipenem. 21,22 E. coli showed high resistance to cefuroxime (76.1%) and ceftriaxone (71.4%), followed by norfloxacin (61.9%).…”
Section: Discussionmentioning
confidence: 99%
“…High sensitivity of E. coli to Imepenem has also been documented by Patel et al (100%), Gupta et al (96%) and Sharan et al (58%). [12][13][14] In present study, the pathogens which were commonly seen below 1 month of age were either Enterococci (2 cases) or E. coli (1 case). These neonates were in septicemia with intravenous lines that predisposed them to Enterococcal infection.…”
Section: Discussionmentioning
confidence: 99%